Implementasi Sistem Keuangan Desa Terhadap Pengelolaan Keuangan di Desa Mekarmulya Kabupaten Karawang - Zelza Rachma Nur Alifah; Maulana Rifai; Lina Aryani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to identify and analyze the implementation of the village financial system (Siskeudes) on village financial management in Mekarmulya Village, Telukjambe Barat District, Karawang Regency. This research is a type of qualitative research by collecting data through interviews, observation, and documentation as well as literature studies. The informant in our study was the Head of Mekarmulya Village Finance, Mr. Darma. Based on the research results, the implementation of the Siskeudes in Mekarmulya Village was first implemented in 2017 and began to be used in 2019. The implementation of the Siskeudes in Mekarmulya Village is considered to be quite good in terms of utilization and transparency of village finances. But behind that, there are still some obstacles in its implementation, namely inadequate facilities and infrastructure such as a lack of supplies of laptops and internet facilities which sometimes run slowly. Input from the siskeudes application is in the form of data that is entered, namely planning, budgeting, administration, and bookkeeping data. While the output of the Siskeudes application is in charge of making reports of programs that have been run by the Village Government of Mekarmulya for one full year. Overall, the implementation of the Siskeudes in Mekarmulya Village, Karawang Regency has been considered quite good, although there are still some deficiencies that must be fixed and considered.